Summary of the state of Costa Rican active volcanoes during 2012-2013 - Alpízar, Yemerith (2014)
As part of the tasks of Red Sismológica Nacional of Costa Rica (RSN, UCR-ICE), volcanic monitoring is a topic that need all our attention. Likewise, the record of the results from this monitoring (field and laboratory work), is a useful tool for the research in short, middle and long term. This tecnic note comprises a synthesis of the results and observations of the last two years of volcanic surveillance at active volcanoes in Costa Rica (Rincón de la Vieja, Arenal, Poás, Barva, Irazú and Turrialba). These results enrich the RSN data base, covering four decades of experience in the implementation of advanced technologies in the area. In the beginning of 2012 all volcanoes manifested background behavior, representing low levels of phreatic and seismic activity. In September 2012, an increase in volcanic activity occurred following the Samara earthquake (Mw=7,6). This increased unrest was manifested mainly through the increase in temperature of fumaroles, some changes in crater lake dynamics and chemistry, increased seismic and phreatic activity. These higher activity conditions were maintained during the rest of the period.